PENINGKATAN PEMAHAMAN SISTEM PEMINDAH DAYA TRANSMISI MANUAL 5K BAGI SISWA SMK MA’ARIF NU TALANG - Amin Nur Amin Nur Akhmadi (JP3M: Jurnal Pendidikan, Pembelajaran dan Pemberdayaan Masyarakat, 2022)
The growing automotive world demands changes so that transportation is better, not only in its fuel-efficient engines but also at the level of comfort in driving. One of them is the change in the transmission system Now there are two transmission systems, namely manual transmission and automatic transmission. Manual transmission is one type of transmission that is widely used for reasons that are more efficient and more agile to face road terrain. Automatic transmission or known as Continuous Variable Transmission (CVT). The activity method that will be conveyed to the students at Smk Ma'arif Nu Talang Tegal Regency in the form of improving the understanding of the 5K manual transmission power transfer system, students are also equipped with a way of overhauling sychromes replacement for transmission This community service activity produces the following results: The following: (1) Improving human resources, especially vocational students who have professional skills, with skills, knowledge, and work ethic in accordance with the demands in automotive (2) Introducing students to work and overhauling 5K manual transmission in the world of industry and perbengkelan so that in time they enter the field of work in the world of perbengkelan that can actually adapt quickly (3) Prepare quality human resources that are in accordance with the needs in the era of automotive engineering technology. From the results of community service activities in Smk Ma'arif Nu Talang tegal regency concluded as follows: (1) With the community service activities in Smk Ma'arif Nu Talang Tegal Regency, it provides knowledge, understanding on vehicles that transmit efficient 5K manuals according to the operational standards of safety procedures (2) After going through several stages in community service activities, especially at SMK Ma'arif Nu Talang, Students majoring in Light Vehicle Engineering / very proud to have been able to do maintenance and overhaul work, understanding and practice about 5K manual transmission on light vehicles.